Pengaruh Penggunaan Media Audio Visual Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Administrasi Umum Kelas X OTKP diSMKN 4 Surabaya - Tasya Gilar Ambarini Sukma; Durinta Puspasari (Edunusa: Journal of Economics and Business Education, 2021)
The purpose of this study was to determine the effect of using audiovisual media on the learning motivation of class X OTKP students in general administration subjects at SMKN 4 Surabaya. This research is a research that uses quantitative methods. The population of this study as a whole consisted of all OTKP Class X students and 105 students, and the sample for this test was 84 students using proportional random sampling. The method of collecting information in this research is a closed survey in the form of a questionnaire. Tests in this study include validity and reliability. The data analysis method used the classical hypothesis test which combines the normality test with the heteroscedasticity test and the hypothesis test using a simple linear regression test. So the results of simple linear regression analysis for a significance value of 0.000 can be concluded that the use of audiovisual media has a significant effect because the significance value is smaller than <0> t table or 20.722> 1.659. Affect students' learning motivation